Enantioselective Synthesis of 1-Substituted 1,2,3,4-Tetrahydroisoquinolines through 1,3-Dipolar Cycloaddition by a Chiral Phosphoric Acid - Jin, Yuan; Honma, Yasuhiro; Morita, Hisashi; Miyagawa, Masamichi; Akiyama, Takahiko (Synlett, 2019)
A new approach is described for the asymmetric synthesis of 1-substituted 1,2,3,4-tetrahydroisoquinolines that is based on the enantioselective 1,3-dipolar cycloaddition reaction of a nitrone and a vinyl ether in the presence of a chiral phosphoric acid that gives the chiral tetrahydroisoquinolines in high yields and with high enantioselectivities. 1H and 31P NMR analyses of the mixture of nitrone and chiral phosphoric acid suggest the formation of a 1:1 complex.
Keywords: phosphoric acids; asymmetric synthesis; 1,3-dipolar cycloaddition; nitrones; vinyl ethers; tetrahydroisoquinolines